Mesh adaptivity in finite elements using the mortar method - Bernard, Christine; Maday, Yvon (European Journal of Computational Mechanics, 2000)
Relying on the mortar element technique, we propose an algorithm for mesh adaptivity in finite elements, where no conformity condition is enforced on the intersection of the triangles during the refinement process. We perform the numerical analysis of the final discretization.